Advanced Phenotyping of Otosclerosis in an Ontario Population and Two Large Newfoundland Families - Lucas, Matthew B (Scholarship@Western, 2020)
Otosclerosis is a relatively common hearing loss disorder characterized by abnormal bone growth in the otic capsule leading to stapes fixation. In approximately half of cases, otosclerosis is inherited as an autosomal dominant trait. Typically, gene discovery efforts rely on surgical confirmation, audiometry and occasionally acoustic reflexes to identify affected cases of otosclerosis within families, requiring that the otosclerosis was at an advanced stage to be detected. This makes it difficult to identify individuals with early otosclerosis. The use of advanced phenotyping to identify cases of otosclerosis was tested in an Ontario otosclerotic population as well as in two large Newfoundland families, one with otosclerosis due to a newly discovered deletion in the FOXL1 gene. Family history questionnaires revealed that approximately two-thirds of Ontario probands had a significant family history of non-congenital hearing loss with almost half of those probands reporting another family member with otosclerosis. Furthermore, all Ontario probands were screened for the FOXL1 deletion identified in the NL family, with one testing positive, providing evidence that FOXL1 may underlie cases of otosclerosis in other populations. The otosclerotic phenotype of prospective data obtained in a surgically-confirmed Ontario cohort was quite variable with 30% of subjects presenting with unilateral otosclerosis and 9% presenting with sensorineural hearing loss (SNHL) in their non-surgical ear. Results suggest that distortion product otoacoustic emissions and acoustic reflex thresholds are absent in all surgical ears, SNHL ears and ears with a conductive hearing loss. To further enhance the advanced phenotyping of otosclerosis, power absorbance (PA) was analyzed to determine its utility as a phenotyping tool. Results suggest that PA has a valid test-retest reliability, but that instrument and stimulus effects are present. Advanced phenotyping was used to develop a predictive model for FOXL1-associated otosclerosis suggesting a ...